Peningkatan Kapasitas Produksi Pada Home Industry Gudang Terasi Udang Kecamatan Meureubo, Aceh Barat - Rahmawati; Syarifah Zuraidah; Teuku Amarullah; Zuriat (Universitas Serang Raya, 2024)
Aceh Barat Regency is directly facing the sea and has many local potentials that can be utilized, including rebon shrimp. In the rainy season, many rebon are caught, but in the dry season, many small fish are caught. People usually sell fish and rebon directly at very low prices. Pumpkin shrimp, which are dried, are then resold. As one of the perishable fishery products, prawn shrimp must be processed so that it can last for a long time. For years, shrimp paste warehouses have been processing rebon into shrimp paste. However, the industry has not maximized its production. Therefore, there was a training to increase the production capacity of shrimp paste by using printing aids, which can produce more shrimp paste in one printing process. This training is intended to improve the ability of industrial houses to produce products with time efficiency in production. The training assisted industrial houses in streamlining the shrimp paste production process, allowing them to increase their production capacity in a single production run. In addition, terasi business owners received training on product branding to increase sales and expand the market, thereby increasing revenue.